Impact of requirements volatility on software architecture: How do software teams keep up with ever‐changing requirements?. Issue 6 (25th March 2019) - Dasanayake, Sandun; Aaramaa, Sanja; Markkula, Jouni; Oivo, Markku
Abstract: Requirements volatility is a major issue in software development, causing problems such as higher defect density, project delays, and cost overruns. Software architecture that guides the overall vision of software product is one of the areas that is greatly affected by requirements volatility. Since critical architecture decisions are made based on the requirements at hand, changes in requirements can result significant changes in architecture. With the wide adoption of agile software development, software architectures are designed to accommodate possible future changes. However, the changes has to be carefully managed as unnecessary and excessive changes can bring negative consequences. An exploratory case study was conducted to study the impact of requirements volatility on software architecture. Fifteen semistructured, thematic interviews were conducted in a European software company. The research revealed poor communication, information distortion, and external dependencies as the main factors that cause requirement volatility and inadequate architecture documentation, inability to trace design rationale, and increased complexity as the main implications of requirements volatility on software architecture. Insights from software teams' awareness of the requirement volatility, factors contribute to it, and possible ways to mitigate its implications will be utilized to improve the management of requirement volatility during software architecting process. Abstract : This case study provides empirical evidence on the relationship between requirements and software architecture, and how changes in one can affect the other. The study identifies the factors that contribute to requirement volatility as well as how requirement volatility can have adverse implications on software architecture. A two‐pronged approach is proposed to address the issue by mitigating the negative implications of requirements volatility on software architecture and preventing their recurrence.